Testing associations between language use in descriptions of playfulness and age, gender, and self-reported playfulness in German-speaking adults - Brauer, Kay; Sendatzki, Rebekka; Proyer, René T. (Frontiers in Psychology, 2022)
Adult playfulness describes individual differences in (re)framing everyday situations as personally interesting, and/or entertaining, and/or intellectually stimulating. We aimed at extending initial evidence on the interconnectedness between language use and adult playfulness by asking 264 participants (M = 26.5 years, SD = 9.7; 66.7% women) to provide written descriptions of their understanding of playfulness (mean length: 30.6 words; SD = 24.1) and collected self-reports of their playfulness. We used the Linguistic Inquiry and Word Count methodology to quantitatively analyze the language use in these descriptions and tested the associations with individual differences in participants’ age, gender, and playfulness. While higher expressions in all measures of playfulness did go along with writing more content when describing playfulness (rs =.13 to .25), facet-wise analyses revealed differential findings (e.g., Intellectual playfulness relates to using words describing cognitive processes); but the effects were small. We found that being a women and younger age related to writing longer texts (.13 ≤ rs ≤ .24), and we discovered additional associations between certain LIWC categories and age and gender. Our study expands the knowledge about adult playfulness and its manifestations in natural language use. We embed our findings into previous research and discuss limitations and potential approaches for replication studies.